Efektivitas Pijat Bayi Terhadap Gangguan Gumoh Pada Bayi Umur 0-3 Bulan Di Latumi Health Care Padang - Hasanalita Hasanalita; Yen Risa Sanputri (Jurnal Ventilator, 2023)
Regurgitation or often called spitting up is the passage of refluxed gastric contents into the pharynx or mouth, sometimes with expulsion from the mouth. Complications that occur when excessive spitting up causes Gastroesophageal Reflux, which is backflow from the stomach to the esophagus which causes damage to the esophageal wall. In Indonesia, the incidence of spitting up in infants aged 2 months is higher than other countries. 25% of babies spit up >4 times during the first month, 50% spit up 1-4 times a day until 3 months of age. 30% of mothers also experience anxiety about spitting up, where anxiety is related to spitting up frequency of 66% and spitting up volume of 9%. As well as symptoms that accompany spitting up such as crying and fussing. (IDAI, 2016). This type of research is experimental (experimental research) with a one shot case study/post test only design approach. The population in this study were all infants aged 0-6 months. The sampling technique in this study was carried out using a non-probability sampling technique, namely the type of purposive sampling technique, with a total sample of 16 people. The instrument used is the observation sheet. The univariate analysis aims to explain or describe the distribution of spitting up frequencies in infants before and after massage. For numerical data, the mean or average value is used, and for categorical data, the chi-square is used. This study uses the Shapiro Wilk normality test to determine whether the data is normally distributed or not. Then a paired sample T-test was performed. The average value of spitting up before baby massage is 0.500 with a standard deviation of 0.516. The average value of spitting up after baby massage is done with an average value of 0.686 with a standard deviation of 0.479. The results of the statistical test using the Paired T-Test obtained a p value of 0.003, which means that Ho was rejected, so it can be concluded that there is a difference in the frequency of spitting up before and after baby massage. There are differences in spitting up disorders in babies who are massaged and not massaged. Where the average baby who was massaged did not spit up while the baby who was not massaged had spit up.